Addressing the immigrant screening gap: A protocol for a systematic review on interventions to enhance colorectal cancer screening among immigrants in the United States - Taylor M. McCready; Ethan M. Cohen; Gregory Laynor; Perla Chebli; Peter S. Liang; Audrey Renson (PLoS ONE, 2025)
Introduction Colorectal cancer (CRC) screening rates are lower among immigrant populations in the United States (US) than the general population. Immigrant communities face structural barriers that disincentivize their engagement from CRC screening. A growing body of literature has evaluated the effects of interventions aimed at increasing CRC screening engagement among various immigrant groups, but there has not yet been a systematic synthesis of this literature. Objective This review will systematically evaluate quantitative studies assessing the effects of interventions designed to increase CRC screening rates among immigrant populations residing in the US. Methods We will conduct a comprehensive search of English language peer-reviewed and grey literature using specific keywords and database-specific structured vocabulary on interventions to improve CRC screening rates among immigrants published in 7 databases (PubMed, Cochrane Library (Wiley), CINAHL (EBSCO), ClinicalTrials.gov, Embase (Ovid), Scopus (Elsevier), and Web of Science) from January 1, 2000 to December 31, 2024. All studies will be imported into Covidence. Two reviewers will independently screen titles, abstracts, and full-texts for inclusion and exclusion criteria. Pilot screenings and consensus discussions will ensure accuracy and agreement in study selection and data extraction. Iterative data extraction of eligible studies will include critical appraisal using the Risk of Bias 2 (ROB2) for randomized controlled trials, while other study designs will be appraised with the risk of bias in nonrandomized studies of interventions (ROBINS-I) tool. Data synthesis will disaggregate pooled effect estimates by ethnicity, to the extent possible. The study protocol was pre-registered in International Prospective Register of Systematic reviews (PROSPERO): CRD42023488183. Expected outputs This systematic review aims to generate an exhaustive summary of the evidence base, including a description of the intervention methods and settings, target populations, recruitment and retention strategies, partnerships and collaborations, and reported outcomes. The results will provide actionable recommendations for public health practitioners, healthcare providers, and policymakers developing tailored interventions and policies aimed at improving CRC screening uptake among diverse immigrant populations in the US.